PENGEMBANGAN KONSEP EKONOMI SYARI’AH DALAM UU NO. 3 TAHUN 2006 TENTANG PERUBAHAN ATAS UU NO. 7 TAHUN 1989 TENTANG PERADILAN AGAMA - Anita Marwing (MUAMALAH, 2014)
The scope of syari‟ah economy in fikih muamalah is very large. If it is compared with the explanation in the article of 49 UU RI Number 3, 2006 about the change of UU Number 7, 1989 about The Religious Court. It means that syari‟ah economy not only covers bank of syari‟ah, insurance, reinsurance. Reksadana, pawnshop, finance of syari‟ah and etcetera but also all forms of rights problem, things, and property, a binding agreement or contract in terms of both of them. It is done based on the principle of fikih muamalah.